Changes in Intra-industry Competitiveness of the New Member States (EU-10) Economies During the Crisis, the Years 2009-2011 - Molendowski, Edward; Polan, Wojciech (Comparative Economic Research. Central and Eastern Europe, 2013)
The global financial crisis, mostly triggered by external factors, interrupted the trend toward enhanced strength of the EU-10 economies, which was the outcome of the solid structural reforms carried out in the pre-accession era. In this regard, this article investigates the following research problem: what have been the changes in intra-industry competitiveness of the new member states (EU-10) economies during the crisis, and to what degree have the positive adaptive processes taking place in the structures of their economies before and after their accession to the EU - which reflected the extent of their preparations for full integration with the single EU market - been influenced by this crisis? This paper aims to present the main results of our analysis of changes in the trade flows of the examined countries in the initial years after the accession (2003-2008), and subsequently during the crisis (2009-2011). It especially focuses on presenting the main tendencies in intra-industry trade development in mutual trade among the new member states and with the EU-15 countries, and the main changes in a vertical and horizontal intra-industry specialization.